A STUDY OF THE DIFFERENCES IN LEARNING MOTIVATION BETWEEN MALE AND FEMALE LEARNERS IN INTENSIVE ENGLISH COURSES - Mardiansyah Mardiansyah (Language-Edu, 2021)
Motivation alludes to the mix of exertion and desire to accomplish the objective of learning the language to great perspectives toward learning the language. The reason for this examination are; first, to analyze the differences in motivation between male and female learners. Second, to analyze the correlation between motivation and proficiency of the learner learning English in intensive courses. This research is a quantitative research which require numerical data. The population in this study were 140 respondents learning English in intensive courses. The researcher conducted this research by online because of covid 19. The data questionnaire are collected by Google form. The data obtained were analyzed by SPSS using independent t-test formula. It showed that male learners have better motivation than female learners in learning  English in intensive courses. Male learners tend to get over female on different measures like instrument orientation on the one side and international oriented and self-regulation on the other side. Also, it revealed that motivation was strongly affect learners achievement. It said that the correlation coefficient is 0.350 in which indicated that the correlation was weak between two variable.